Performance-based funding: A case study in Madagascar - Cochran, Seth (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To successfully introduce a digital performance-based funding system into Sambava Hospital in the SAVA region of Madagascar in order that surgeons and clinical care workers would be incentivized to provide high-quality care to a greater number of patients. Methods: We used a combination of monetary and non-monetary incentives, the first is that we provide a cash transfer when Dr. Fidèle and his team perform in line with our minimum standards of care; the quality of surgery and the entire continuum of care is measured by the use of Operation Fistula’s Global Obstetric Fistula Electronic Registry (GOFER) application. The non-monetary incentives include visualisations of Dr. Fidele’s surgical progress so that he can more effectively monitor the practices of the team. Results: This pilot in Sambava Hospital revealed that the data collection tool serves three purposes: It ensures that the surgeries performed and nursing care maintained meet a minimum standard of care; It acts as a verification mechanism that triggers payment; and The data collected enables Dr. Fidèle to track and measure his own surgical progress, with our surgical dashboards. Conclusions: The initial outcome of this pilot program has yielded positive results. From March to September, the treatment of 40 patients has been accounted for and transfers have been made, on receipt of corresponding data. Keywords: Funding, high quality care, patients